Normalization in Database Design. - Atanacio, Edgardo G. (Philippine Engineering Journal)
The design of database files can be improved with the use of normalization. Normalization simplifies the structure of database files by grouping the components into simpler structures. Such simple structures adapt better to changes or modifications to the database which are usually necessary to meet changing needs. This paper describes the procedure of converting unnormalized files to the Third Normal Form.